Detection and genotyping of Anaplasma phagocytophilum in I. persulcatus and D. reticulatus ticks collected in Tomsk (Western Siberia) in 2015–2016 - M. Yu. Kartashov; T. P. Mikryukova; N. S. Moskvitina; E. I. Krivosheina; A. I. Kuznetsov; V. N. Romanenko; N. P. Bol’shakova; V. A. Ternovoi; V. B. Loktev (Бюллетень сибирской медицины, 2019)
Introduction. The detection of the first cases of tick-borne human granulocytic anaplasmosis in Russia, discovery of genetic markers for Anaplasma spp. in ixodid ticks and reporting of a significant number of cases of tick-borne infections in the southern part of Western Siberia give reason to suppose that causative agents of tick-borne anaplasmosis may be transmitted in Tomsk and its suburbs. Objective. To study the distribution and species biodiversity of A. phagocytophilum in ixodid ticks in Tomsk Region. Materials and methods. The analysis of 690 individual ixodid ticks (larvae and adults) was carried out for Ixodes persulcatus (n = 530) and Dermacentor reticulatus (n = 160) ticks collected in 2015–2016 on the territory of urban and suburban biotopes of Tomsk. Primary screening of ticks for the presence of genetic material of A. phagocytophilum was conducted using two-round PCR with species-specific primers for the 16S rRNA gene. The amplification (1,220 kB) of the groESL fragment of the heat shock protein operon was performed for positive isolates with subsequent determination of the nucleotide sequence in the gene fragment for phylogenetic analysis. Results. The number of A. phagocytophilum positive samples for I. persulcatus (larvae) was 1.2 ± 0.6%, I. persulcatus (adult) was 1.8 ± 0.7%; and D. reticulatus (adult) was 0.6 ± 0.3%. Analysis of the nucleotide sequence of the gene fragments in groESL operon for nine isolates confirmed that the genetic material of the granulocytic anaplasmosis was detected. Phylogenetic analysis showed that all the isolates belonged to the first group of the “new cluster” of A. phagocytophilum. Conclusion. The causative agent of human granulocytic anaplasmosis has been newly detected in I. persulcatus ticks collected in urban and suburban biotopes of Tomsk and in D. reticulatus from urban foci.